L’impact de la morpho-syntaxe dans les processus de métaphorisation contrastive entre langues romanes et germaniques - Trim, Richard (Neophilologica, 2018)
This study will examine the role of morpho-syntactic structures in the creation of metaphor from a contrastive point of view and in relation to Romance and Germanic languages. Within the framework of cognitive linguistics, the analysis suggests that morpho-syntax, as a part of the linguistic component largely neglected in cognitive research concerning metaphor creation, plays an important role in literary innovations. This appears to be the case in the formation of composite adjectives. In line with the impact of physiological and sensory conceptualization proposed by Cognitive Metaphor Theory, it seems that morphologies related to the Romance and Germanic languages also contribute to the creation of a literary style arising from the morphology concerned. Stylistic effects thereby appear to vary between these two language groups. Additional constraints may arise within one language group, however, due to semantic features in morphemic order and collocations.